2020
DOI: 10.1111/bju.15268
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging‐guided transurethral ultrasound ablation in patients with localised prostate cancer: 3‐year outcomes of a prospective Phase I study

Abstract: S.M.N. and G.H. contributed equally towards the data analysis and article preparation. ObjectivesTo report the 3-year follow-up of a Phase I study of magnetic resonance imaging (MRI)-guided transurethral ultrasound ablation (TULSA) in 30 men with localised prostate cancer. Favourable 12-month safety and ablation precision were previously described. Patients and MethodsAs a mandated safety criterion, TULSA was delivered as near whole-gland ablation, applying 3-mm margins sparing 10% of peripheral prostate tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…For the 22 men with a complete 3-year follow-up, 13/22 and 11/22 had erections sufficient for penetration at baseline and follow-up. 12 For the 16 men with a complete 5-year follow-up, 9/16 and 7/16 had erections sufficient for penetration at baseline and follow-up. 13 …”
Section: Evidence Synthesis and Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For the 22 men with a complete 3-year follow-up, 13/22 and 11/22 had erections sufficient for penetration at baseline and follow-up. 12 For the 16 men with a complete 5-year follow-up, 9/16 and 7/16 had erections sufficient for penetration at baseline and follow-up. 13 …”
Section: Evidence Synthesis and Resultsmentioning
confidence: 98%
“…Feasibility was also assessed in a prospective Phase I study ( n = 30) 11 with up to 5-year follow-up. 12 , 13 However, a nononcologic treatment plan was applied and the intent of the study was to assess the feasibility and not to achieve definitive treatment. Therefore, the rates of salvage treatment, clinically significant disease, MRI recurrence, and BCR from the Phase I study were not included in the present synthesis.…”
Section: Evidence Synthesis and Resultsmentioning
confidence: 99%
“…Routine follow-up biopsy at 12 months is therefore recommended to ensure timely detection of residual disease. For patients with tumor recurrence, standard salvage treatments like radical prostatectomy ( 19 ) or radiotherapy ( 20 ) are viable options.…”
Section: Discussionmentioning
confidence: 99%
“…At 12-month follow-up, 9/29 (31%) patients had a positive 12-core transrectal, US-guided biopsy for csPCa (GG1 >10mm, GG2 >3 mm, or any GG3 disease), while 16/29 patients had a positive biopsy for any disease ( 36 ). A subsequent study completed 3 years of follow-up in 22 individuals from the original study ( 39 ), during which no new serious or severe adverse events were reported. Erectile function and PSA levels were also stable at 3 years.…”
Section: Transrectal Mr Guided Focused Ultrasound Surgery (Mrgfus)mentioning
confidence: 99%
“…Erectile function and PSA levels were also stable at 3 years. Overall, 10/29 (34%) participants had csPCa at 3 years, including 19 men who had repeat biopsy at the 3-year mark, and 10 men who only completed biopsy at 12 months ( 39 ).…”
Section: Transrectal Mr Guided Focused Ultrasound Surgery (Mrgfus)mentioning
confidence: 99%